Application of FOCUS-PDCA management mode in standardizing medication of ophthalmic drugs in patients undergoing ambulatory eye surgery (基于FOCUS-PDCA程序规范眼科日间手术患者眼部用药的实践) - FANG Lin (方琳); HUANG Lan (黄兰); WANG Yuan (王媛); LUO Linzhi (罗林芝); LIAO Furong (廖芙蓉); LI Sulian (李素莲) (Journal of International Translational Medicine Limited, 2023)
Objective To investigate the effect of FOCUS-PDCA management mode in standardizing medication of ophthalmic drugs in patients undergoing ambulatory eye surgery, and provide reference for continuous improvement of the nursing quality of ambulatory eye surgery. Methods A non-concurrent control trial was conducted, and patients undergoing ambulatory eye surgery were assigned to the control group (n=146)and the observation group (n=154). The control group received routing nursing management during operation period. The FOCUS-PDCA management mode was adopted in standardizing medication of ophthalmic drugs for patients in the observation group. The rate of qualified self-medication of ophthalmic drugs, awareness and knowledge about ophthalmic drugs and patient satisfaction were measured and compared between groups. Results The rates of proper storage of ophthalmic drugs, proper administration time of ophthalmic drugs and qualified self-medication of ophthalmic drugs in the observation group were higher than those in the control group (P<0. 05). The rates of awareness on storage, administration time and self-medication method of ophthalmic drugs in the observation group were higher than those in the control group (P<0. 05). The score of patient satisfaction in the observation group was higher than that in the control group(P<0. 05). Conclusions FOCUS-PDCA can effectively improve the standardization of self-medication of ophthalmic drugs in patients undergoing ambulatory eye surgery, increase their health beliefs, improve their self-care ability, and promote the postoperative rehabilitation (目的 探讨运用FOCUS-PDCA程序规范眼科日间手术患者眼部用药的实践效果, 为持续提升眼科日间手术护理质量提供参考依据。方法 采用非同期对照设计, 选取在西南医科大学附属中医医院眼科行日间手术患者作为研究对象, 将2022年4月-6月146例手术患者设为对照组, 采用常规围手术期管理; 将2022年7月-9月154例手术患者设为观察组, 按照FOCUS-PDCA持续改进措施开展眼部用药规范化管理。对比两组患者眼部药物使用正确率、眼部用药相关知识知晓率, 评价患者满意度。结果 观察组眼部药物储存、眼部药物使用时间、眼部药物使用方法正确率高于对照组, 差异有统计学意义(P<0. 05)。观察组眼部药物储存方法和眼部药物使用时间知晓率高于对照组, 眼部药物使用方法掌握率高于对照组, 差异具有统计学意义(P＜0. 05)。观察组满意度评分高于对照组, 差异具有统计学意义(P＜0. 05)。结论 FOCUS-PDCA模式能够进一步规范眼科日间手术患者眼部药物使用, 提升患者健康信念和自护能力。)